Análise de práticas de performance de Daniel Guedes no Concerto para violino e orquestra op. 29, de Henrique Oswald - Bárbara Bianca Carvalho Soares Souza (2025)
This doctoral thesis examines Daniel Guedes’s performance of Concerto for Violin and Orchestra, Op. 29, by Henrique Oswald, through an analytical approach that articulates both qualitative and quantitative procedures. The investigation focuses on six specific parameters of violin performance: bowings, fingerings, portamenti, vibrato, dynamics, and rhythmic realization. The research is based on six primary sources — including an audiovisual recording of the performance (2015), two autograph manuscripts, and different editions of the work — and makes use of graphical representations such as audio spectrograms and video frames, generated through the software Adobe Audition and Sonic Visualiser, with the aim of measuring and visually examining interpretative performance data. The analytical process involves a systematic comparison between the performance and the notational indications in the manuscripts, combining attentive listening with spectrographic reading of sonic evidence. The data reveal recurring interpretative tendencies in Guedes’s performance, such as the use of upward bowings to intensify phrase endings, fingerings oriented by timbral considerations, and portamenti applied to promote expressive continuity without undermining structural articulation. The vibrato displays variation in both rate and depth, often correlated with dynamic contour and melodic shape. Rhythmic realization, in turn, includes deliberate temporal fluctuations — such as accellerando and allargando — integrated into the narrative unfolding of the work. These technical-interpretative practices result in a reading that aligns with the aesthetics of late Romanticism and highlights the expressive resources embedded in Oswald’s writing. The research culminates in the development of three supplementary materials: (1) a performance edition with corrections based on comparative analysis of sources; (2) a spectrographic edition of the performance (EdEsP), which graphically systematizes relevant sonic elements; and (3) a structured analytical guide for observing technical-expressive parameters in violin performance, with potential adaptability to other instrumental practices. In doing so, the study proposes an analytical pathway that seeks to reconcile observational precision with an appreciation of interpretative plurality, offering a basis for future investigations in the field of performance studies.